Analysis of Business Strategy Development Using the Business Model Canvas Approach - Wahyu Wirati, Triantya; Umayah, Siti; Irmani Putra, Fadhil; Febriyanti, Febriyanti; Renaga Shafar Anggara, Muhammad; Al-Fathia Laksana, Shifa; Aziz, Wildan (Jurnal Ilmiah Manajemen Kesatuan, 2024)
The increase in fast-paced lifestyles and demands for time efficiency have made consumers more likely to opt for convenience foods. Frozen food is an attractive option due to its ease of storage, preparation, and longer shelf life. To optimally utilize this business opportunity, an in-depth analysis of the right business development and implementation strategy, such as Business Model Canvas, is required. In this research, the method used is descriptive research with a qualitative approach. The data used in this research are primary data obtained from observations of Rajawali Sosis Bakso and secondary data sourced from social media and business literature. The data that has been obtained is analysed qualitatively through three stages. The first stage, compiling the data obtained from the field, then entered into the mapping of the nine BMC elements. The second stage, analysing the BMC using SWOT analysis. The third stage is to formulate a new business model obtained from SWOT analysis, then put it into BMC mapping. Through the Business Model Canvas approach at Rajawali Sosis Baso, there are three elements that need to be improved, namely Key Resources, Cost Structure and Customer Relationship.